Early hyperaesthesia and late hypoaesthesia as manifestations of sensory neuropathy in dentistry – two case reports - Lipták, Laura; Lipták, Klaudia; Kempler, Péter; Hermann, Péter; Rózsa, Noémi Katinka; Balaton, Gergely; Végh, Dániel; Menyhárt, Adrienn; Körei, Anna; Balogh, Dóra Marietta; Bányai, Dorottya (Frontiers in Endocrinology, 2026)
Diabetic neuropathy may present with a wide spectrum of sensory manifestations in the oral cavity, ranging from increased sensitivity to pain to impaired nociception. Early detection is crucial, since the changes have significant effects on dental treatment, patient safety and quality of life. We describe two contrasting pictures of patients with diabetes mellitus with signs of oral sensory neuropathy. The first case was a 14-year-old female with poorly controlled type 1 diabetes mellitus (T1DM) presenting with chronic carious lesions, gingivitis, and angular cheilitis. She also had amplified pain reactions to dental procedures despite adequate local anaesthesia and quantitative sensory testing revealed hyperaesthesia related to early diabetic neuropathy. The second patient was a 55-year-old male with a long-term history of type 2 diabetes mellitus (T2DM) with chronic periodontitis and reduced oral sensitivity. He complained of hypoesthesia and reduced pain perception during dental procedures with evidence of established neuropathic involvement. These cases illustrate the broad spectrum of clinical manifestations of diabetic sensory neuropathy in stomatology from early hyperaesthesia in a child with T1DM to late hypoesthesia in an adult with T2DM and illustrate the importance of metabolic control, interdisciplinary collaboration and individualised diagnostic and therapeutic strategies in dentistry.